Perilaku Mengosok Gigi Kebiasaan Makan dan Minum Tinggi Sukrosa dengan Kejadian Karies Gigi pada Siswa Di MIN Jejeran - Nita Listian Purnamasari; Th Ninuk Sri Hartini; Herawati Herawati (JURNAL NUTRISIA, 2017)
Background: One of the biggest dental health problems experienced by school children is dental caries. Dental caries occurs due to poor tooth brushing behavior and bad eating and drinking habits of bad sucrose. Objective: To know the relationship between the behavior of brushing teeth, eating habits and drinking high sucrose with the incidence of dental caries. Method: The type of this study included observational research with cross sectional study design. The study was conducted at MIN Jejeran 2 in February to May 2017. The research subjects were grade I to V students who were presented in and were willing to be respondents totaling 274 students. The research variables are the behavior of brushing teeth, eating habits and drinking high sucrose, and dental caries. Result: The study showed that dental caries in male pupils 96 students (35%), higher than female 84 students (30.7%). The majority of 266 students (97.1%) had brushing behavior with good behavioral categories. High sucrose foods that are often consumed by students are; Crackers, sweets, biscuits, and sweetbreads. High sucrose drinks that are often consumed by students are tea and homemade milk. Data analysis used Chi-Square and OR (Ood Ratio) test. Conclusion: There was no significant correlation between toothbrushing behavior with dental caries occurrence (p> 0,05). There was a significant relationship between the behavior of brushing teeth with the habit of eating and drinking high sucrose (p <0.05). Keywords: brushing teeth, eating and drinking high sucrose, dental caries